2006
DOI: 10.4049/jimmunol.177.8.5365
|View full text |Cite
|
Sign up to set email alerts
|

Differential and Nonredundant Roles of Phospholipase Cγ2 and Phospholipase Cγ1 in the Terminal Maturation of NK Cells

Abstract: NK cells play a central role in mediating innate immune responses. Activation of NK cells results in cytotoxicity, cytokine, and chemokine secretions. In this study, we show that in mice with targeted deletion of phospholipase Cγ (PLCγ)2, one of the key signal transducers, there are profound effects on the development and terminal maturation of NK cells. Lack of PLCγ2 significantly impaired the ability of lineage-committed NK precursor cells to acquire subset-specific Ly49 receptors and thereby terminal matura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
40
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 66 publications
(93 reference statements)
4
40
2
Order By: Relevance
“…28 The total number of lymphocytes in the BM, spleen and liver were comparable between WT and p85a À/À mice as previously reported 20 (data not shown). Lymphocytes were divided into T (CD3 þ NK1.1 À ), NKT (CD3 þ NK1.1 þ ) and NK (CD3 À NK1.1 þ ) cells based on their staining patterns.…”
Section: Resultssupporting
confidence: 85%
See 3 more Smart Citations
“…28 The total number of lymphocytes in the BM, spleen and liver were comparable between WT and p85a À/À mice as previously reported 20 (data not shown). Lymphocytes were divided into T (CD3 þ NK1.1 À ), NKT (CD3 þ NK1.1 þ ) and NK (CD3 À NK1.1 þ ) cells based on their staining patterns.…”
Section: Resultssupporting
confidence: 85%
“…Our previous studies using PLCg2 À/À mice demonstrated a significant reduction in all the Ly49 þ NK subsets, irrespective of their MHC class I ligand preferences. 28 This observation along with our present study indicates that both PLCg2 and p85a are important for subset specifications. Both PLCg2 and PI3K are known to regulate a number of transcription factors.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…As a result of this multiplicity, only a few molecules have been shown to be required for natural cytotoxicity in mouse knockout models. Phospholipase C (PLC)-γ2 is an important mediator of degranulation, cytotoxicity, and cytokine production [38][39][40]. Pharmacological inhibition of PLC-γ abrogates degranulation, cytotoxicity and cytokine production by human NK cells, in addition to early signals for intracellular calcium mobilization [41].…”
Section: Proximal Activation Signalsmentioning
confidence: 99%